Preservice Primary-School Educators' Perceptions of the Usefulness of and Problems With Art Education: A Case Study - Morales-Caruncho, Xana; Chacon-Gordillo, Pedro; Marfil-Carmona, Rafael (Studies in art education, 2022)
Art education has traditionally been considered a discipline related to leisure. A case study of primary preservice generalist educators at a Spanish university was conducted to determine whether or not this perspective has evolved. It was of interest to examine whether preservice educators understand the way in which art education develops comprehensive and analytical skills. This study integrated both qualitative and quantitative methodologies to examine future teachers’ perceptions of the usefulness of this subject and the problems it presents. Outcomes indicate that there is still a long way to go to transform preservice primary generalist teachers’ false perceptions related to art teaching.
Keywords: art education; primary school; Emerging; Scopus